β-catenin-independent roles of Wnt/LRP6 signaling - Acebron, Sergio P.; Niehrs, Christof (Trends in cell biology, 2016)
Wnt/LRP6 signaling is best known for the β-catenin-dependent regulation of target genes. However, pathway branches have recently emerged, including Wnt/STOP signaling, which act independently of β-catenin and transcription. We review here the molecular mechanisms underlying β-catenin-independent Wnt/LRP6 signaling cascades and their implications for cell biology, development, and physiology.
Gesehen am 20.07.2020